Analysis of the conditions for the creation of pharmaceutical university spin-offs within a public university in Burkina Faso - Daniel DORI; Sonia Gampoa NASSOURI; Siéssima Lawakilia Natacha Tchaida Martine TOE DJIGUIMDE; Raogo OUEDRAOGO; Rasmané SEMDÉ (International Journal of Drug Regulatory Affairs, 2024)
This study aimed to analyze the legal framework for the creation of university spinoffs, particularly those in the fields of medicine and pharmacy in Burkina Faso. This was carried out through a literature review, supplemented by interviews with resource persons from the sectors in charge of commerce, industry, finance, scientific research and innovation, health, and youth.In Burkina Faso, there are no specific provisions for promoting university spinoffs. A Simplified Joint Stock Company is the most appropriate legal form for these types of companies. Moreover, these laws do not favor the mobility of researchers in entrepreneurship. In addition, university spinoffs are subject to the same tax pressure as conventional companies. Nevertheless, the University of Joseph KI-ZERBO supported project leaders through its incubator. However, its lack of status, insufficient material, and financial resources limit its actions.